Elements indicating stock price movements: the case of the companies listed on the V4 stock exchanges - Aliu, Florin; Nadirov, Orkhan; Nuhiu, Artor (Journal of Business Economics and Management, 2021)
Stock markets stand as a financial mechanism that provides liquidity for firms and offers diversification benefits for investors. Stock markets in the Eastern European countries are weakform efficient which exposes them to speculative prices. This study investigates the influence of the macroeconomic and firm-specific factors on stock prices of the listed companies within the Visegrad Stock Markets. The study employs regression analyses based on a Pooled OLS and Fixed Effect models with year dummies and standard errors clustered at the country level, which are robust to autocorrelation and heteroscedasticity. Data collection consists of 55 listed companies based on the weekly stock prices, from January 2013 till December 2018. The results indicate that total equity is the only significant element that influences the individual stock prices of the companies in the four established models. Additionally, increase in supply of shares declines the current stock prices and the other way around. However, the exchange rate and inflation level indicate a negative influence on the stock prices with weaker significance. The findings show that stock markets of the V4 countries are overall inefficient since important indicators, such as economic activity, debt level, cash flow, firm size, oil, and gold prices have limited influence on the stock price movements.